Performance of audio-assisted confidential voting interview for assessment of sexual behavior among young adults in Chandigarh Union Territory - Satya Ranjan Lenka; Jarnail Singh Thakur; Prabhat Jha; Rajesh Kumar (Wolters Kluwer Medknow Publications, 2011)
A cross-sectional study was conducted in Chandigarh Union Territory to evaluate the performance of an audio-assisted confidential voting interview (AVI), for assessing the sexual behavior among young adults aged 20 - 34 years. Using systematic random sampling 625 males and 630 females were interviewed alternately, either by AVI or by face-to-face interview (FFI). More men revealed having sex with men in AVI (2.6%) than FFI (0.6%) (P 0.06). Women reported having sex with non-regular partners more often in AVI (4.8%) compared to FFI (0.3%) (P < 0.001). AVI performed better than FFI for eliciting sensitive sexual behaviors.